Penerapan Akuntansi Keuangan Digital Bagi Pelaku UMKM Di Desa Kedungdalem Kabupaten Probolinggo - Rachmanita Eza Putri Wiyandari; Helmy Wahyu Sukiswo (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
In the digital era, people are expected to master and use technology. This also applies to micro, small and medium enterprises. MSMEs must be able to make good bookkeeping both manually and digitally. Digital accounting can be managed with the Bukukas application on a smartphone. The advantage of this application is that it makes recording easy, economical, easy to increase capacity, quality and reporting expertise. Application-based financing so that MSME players can use the BukuKas application independently. This mission was carried out in Kedungdalem Village MSMEs by presenting around 20 people from various types of MSMEs such as flower sales, chips and snacks businesses. The obstacles that are often faced by MSMEs are that there is no record of bookkeeping and financial transactions and some are still recording manually as well. In addition, there are still difficulties in determining profits and inventory levels. Therefore, providing training on how to use the BukuKas application can help them record financial transactions and market their products.